Experiment research and mechanism analysis on rheological properties of tailings slurry - Wang, Zhiliu; Chen, Linlin; Hu, Mengxin (Frontiers in Earth Science, 2023)
The particle size and content of tailings are important parameters affecting the rheological properties of tailings slurry. To explore their influence law and mechanism on rheological properties, the experiments of tailings slurry were designed and carried out under different particle sizes and content conditions. The rheological properties of the tailings slurry were quantified in the paper. The “double 30” theory (“particle size of 30.0μm” and “content of 30%”) was proposed and expounded. The corresponding theoretical model is established to analyze the mechanism of the above results. The conclusion is as follows. The tailings slurry agreeed to different rheological models with different particle size and content. The rheological behavior of the tailings slurry conforms to the Herschel-Bulkley model for the tailings, whose particle size is no larger than 30.0μm and content is no larger than 30%. With the increase of the content of fine tailings, its behavior agrees better with the Bingham model. The yield stress and viscosity of tailings slurry in the process of transportation are in accordance with the laws of “double 30” theory. “Particle size of 30.0μm” and “content of 30%” is the critical point of rheological characteristics of tailings. Based on the obtained results, the corresponding theoretical model was established to discuss the mechanism. The rheological laws of tailings slurry can provide theoretical guidance for reducing pressure and preventing pipeline wear in the process of tailings consolidation discharge and pipeline transportation in an iron mine.